A formação do preceptor multiprofissional: a experiência de um hospital universitário - Eliane Maria Magalhães da Cunha de Melo (2023)
This work consists of a descriptive, exploratory case study on the training of multidisciplinary preceptors in a university hospital, from 2010 to the present day. In 2007, the Health Ministry established the National Policy of Permanent Education in Health aimed at adjusting the professional training and qualification of health workers, whose concepts and principles involve meaningful learning, questioning work processes, and the chain of health care. Medical residencies, multidisciplinary or in the health area, are modalities of Lato Sensu postgraduate courses, in the form of specialization, characterized by in-service training, on an exclusive dedication basis, carried out in health institutions, university or not, under supervision of highly qualified professionals from the education and health sectors. The data collection was carried out in two stages: a documenting analysis to support the study and the description of the background of the residency program and its general characteristics, and interviews with nine multiprofessional mentors and four high-level managers of the hospital. The data organization and analysis were based on the content analysis proposed by Bardin (2004) and two thematic categories were identified: The Professional Training of Multiprofessional Mentors in HC-UFMG and The Work Process of the Multiprofessional Mentor. It was observed that there are no specific programs aimed at the professional training of mentors in the institution, resulting in learning gaps in pedagogical education, a lack of uniformity in learning-teaching practices, as well as insufficient conditions to participate in professional training events. The coordination of the hospital’s residency program faces the challenge of directing the mentor’s work process articulately with the tutors and aligned with the objectives of their political pedagogical project. There have been brief institutional initiatives explicitly aimed at the preparation of the mentors, even though there aren’t enough resources. A significant part of the professional training has been done by each mentor’s initiative; however, it is important to observe that there should be a clear definition of the criteria in order to prioritize the incentive actions for free-choice qualification programs. The results show the need for a proposal of a Qualification Plan for Mentors with clear goals and actions, strategies for following and assessing the professionals who may supervise the work process and subsidize the inclusion of this activity as a performance assessment criterium and professional growth in the institution.